2009
DOI: 10.1016/j.neuron.2009.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Math1 Is Essential for the Development of Hindbrain Neurons Critical for Perinatal Breathing

Abstract: SUMMARY Mice lacking the proneural transcription factor Math1 (Atoh1) lack multiple neurons of the proprioceptive and arousal systems and die shortly after birth from an apparent inability to initiate respiration. We sought to determine whether Math1 was necessary for the development of hindbrain nuclei involved in respiratory rhythm generation, such as the parafacial respiratory group/retrotrapezoid nucleus (pFRG/RTN), defects in which are associated with Congenital Central Hypoventilation Syndrome (CCHS). Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(222 citation statements)
references
References 46 publications
8
213
0
1
Order By: Relevance
“…Moreover, induction at E10.5 labeled cells near multiple medullary nuclei associated with respiration: the rostroventrolateral reticular nucleus (RVL), pre-Bötzinger complex (preBötC), and rostral ventral respiratory group (rVRG) (Fig. 2B, levels 4, 5b, 6b), recently described in further detail (23). Table 1 lists all new and known Math1 hindbrain populations.…”
Section: Novel Math1mentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, induction at E10.5 labeled cells near multiple medullary nuclei associated with respiration: the rostroventrolateral reticular nucleus (RVL), pre-Bötzinger complex (preBötC), and rostral ventral respiratory group (rVRG) (Fig. 2B, levels 4, 5b, 6b), recently described in further detail (23). Table 1 lists all new and known Math1 hindbrain populations.…”
Section: Novel Math1mentioning
confidence: 81%
“…Lhx2 and Barhl2, also Math1-dependent (6, 26), appeared similar to Lhx9 [Movies S1-S48 (AVI)]. [These lineages did not coexpress Phox2b, distinguishing them from recently identified neurons with intraparenchymal Math1 expression (23).] Complete sets of serial sections labeled for each transcription factor in both WT and Math1-null hindbrains are available online [Movies S1-S48 (AVI)].…”
Section: Novel Math1mentioning
confidence: 99%
“…Many of the activities of the proneural factors were delineated by loss-offunction studies in mice and through genome-wide profiling of their transcription targets [48, 49•]. Studies on mouse mutants have shown that homozygous Atoh1 (Atoh1 -/-) and Ascl1 (Ascl1 -/-)-deficient mice both die in the early postnatal period with feeding and respiratory defects [50,51]. Similarly, homozygous Tcf4 knockout (Tcf4 -/-) mice die within 24 h of birth [20,52].…”
Section: The Role Of Tcf4 In Developmentmentioning
confidence: 99%
“…The Atoh1-EGFP+ is a transgenic line in which only a portion of Atoh1 promoter region, is used to drive EGFP. The recently characterized knock-in Atoh1-EGFP mice 141 might be required to solidify the endogenous Atoh1 expression pattern in the future. This result also supports that heterogeneous ectopic Atoh1 levels were detected in different Atoh1-HA+ cells.…”
Section: Atoh1 Dosage Is a Determinant Factor For The Hair Cell Fatementioning
confidence: 99%
“…39,40 To screen for such a drug in a high-throughput manner, mouse embryonic fibroblast cells (MEFs) isolated from Arf is a knock-in mouse model in which the EGFP coding sequence is tagged at the 3' end of Atoh1 gene. 141 MEFs will be treated with different small molecules and turning on EGFP will indicate activation of Atoh1. Thus, EGFP will be used as read-out to judge what small molecules should be used in secondary assays in inner ear cells.…”
Section: Application Of Mouse Pre-clinical Models To Humansmentioning
confidence: 99%